Experience implementing curricular activities in physics to familiarize students with SDGs 5 and 7 - Encina Calvo Iglesias (Feminismo/s)
This paper presents an experience of implementing curricular activities that aim to familiarise students with the Sustainable Development Goals (SDGs), thus promoting sustainability and the critical contextualisation of knowledge and highlighting the scientific contributions of women. The pedagogical experience was carried out in the Physics subject of the Chemical Engineering degree at the University of Santiago de Compostela (USC). First, a questionnaire was administered to assess students’ prior knowledge of these goals, especially SDG 5: «Achieve gender equality and empower all women and girls» and SDG 7: «Affordable and clean energy», in the first-year Physics subjects of the Chemical Engineering and Biotechnology degrees of the USC to determine the influence of the degree. The results showed that students in both degrees knew the SDGs but had difficulties identifying SDG 7. Similarly, male students of Chemical Engineering had more difficulty in identifying SDG 5. Subsequently, the classes, academic content and activities of the Physics subject of the Chemical Engineering degree were planned to raise awareness among students about the current climate, energy and social emergency in which we find ourselves, as well as the gender inequalities that persist in society. In this way, the aim was for students to acquire critical thinking skills to avoid gender blindness and to face a future with fewer and fewer mineral and energy resources. The experience was satisfactory for the students, demonstrating the importance of teaching this content in scientific subjects because they enabled reflection and critical capacity, which are essential for understanding and dealing with reality.